Health Communication Campaign Through Social Media - Evie Sophia; Dewi Indriani Jusuf (International Journal of Education, Information Technology, and Others, 2023)
The fact that the importance of maintaining health and complying with health protocols during the Covid-19 pandemic has been continuously echoed by the University of Pasudan, including via Instagram univ_pasundan, this is one form of the Health Communication campaign, where the University of Pasundan cares about and cares about the pandemic situation Covid-19 is happening in this country. The purpose of this study was to determine the form, content and targets and objectives of the health communication campaign, using a qualitative descriptive study method using the univ_pasundan Instagram social media network. The data collection techniques in this study were observation, in-depth interviews and documentation studies. This research data analysis technique uses the Miles and Huberman model. The results of this study indicate that respondents from univ_pasundan's Instagram social media gave a positive response to the Health Communication Campaign regarding the Covid-19 pandemic. At the end of the research, the researcher provides input to further enrich the forms and content that are in great demand by followers or viewers, by making more varied video forms and more flexible content and reaching layers of society including the millennial generation